PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM PENDIDIKAN KARAKTER PESERTA DIDIK DI ERA DIGITAL - Budiyono, Apri Eka (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
For students, character education (character formation) for the next generation must be very important, especially in the increasingly advanced and developing digital era, so that students have good morals and character for the social life around them. Principal leadership plays a very important role in influencing, motivating, improving and empowering all existing resources to implement student character development in the digital era. The success of the principal in carrying out character education is determined by: first, firmness and discipline in fulfilling every character building order; second, the principal's leadership encourages teachers and other education personnel to carry out character education; third, creating a conducive school climate and culture; fourth, exemplary school principals in the implementation and success of character education for all school children. The leadership role of the headmaster is shown by example and personality which is reflected in his behavior, understanding, abilities and experience as an educational leader and school principal who is a role model for all school members, especially students to realize character education.